Respuesta :

EXPLANATION

The ii says "hence".  This tells you that you must proceed from i above.

Given;

[tex]y=(10x+2)\ln(5x+1)[/tex]

After differentiating in i, we had;

[tex]\frac{dy}{dx}=10\ln(5x+1)+10[/tex]


We now integrate both sides to obtain;

[tex]\int\limits {\frac{dy}{dx}} \, dx =\int\limits {10\ln(5x+1)+10} \, dx[/tex]


This gives,


[tex]y =\int\limits {10\ln(5x+1)} \, dx+\int\limits {10} \, dx[/tex]


We now split the integral to obtain;


[tex]y =\int\limits {10\ln(5x+1)} \, dx+\int\limits {10} \, dx [/tex]



This implies that,

[tex]y =\int\limits {10\ln(5x+1)} \, dx+10x +C[/tex]


We rearrange to get,

[tex]\int\limits {10\ln(5x+1)} \, dx = y-10x +C[/tex]


But

[tex]y=(10x+2)\ln(5x+1)[/tex]


This implies,


10[tex]\int\limits {\ln(5x+1)} \, dx = (10x+2)\ln(5x+1)-10x +C[/tex]


We divide through by 10.


[tex]\int\limits {\ln(5x+1)} \, dx = 2\frac{(5x+1)\ln(5x+1)}{10}-x +\frac{C}{10}[/tex]

NB: The constant C divided by 10 is still a constant.


[tex]\int\limits {\ln(5x+1)} \, dx = \frac{(5x+1)\ln(5x+1)}{5}-x +C[/tex]


If a=5 and b=1 and we substitute, we get a general formula,but they were partially substituted to  get.

[tex]\int\limits {\ln(5x+1)} \, dx = \frac{(ax+b)\ln(5x+1)}{5}-x +C[/tex]